2020
DOI: 10.1302/2046-3758.97.bjr-2019-0315.r1
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of distal radius fractures using wide-awake local anaesthesia with no tourniquet (WALANT) technique

Abstract: Aims We hypothesized that the wide-awake local anaesthesia with no tourniquet (WALANT) technique is cost-effective, easy to use, safe, and reproducible, with a low learning curve towards mastery, having a high patient satisfaction rate. Furthermore, WALANT would be a suitable alternative for the austere and developing nation environments where lack of funds and resources are a common issue. Methods This was a randomized control trial of 169 patients who required surgery for closed isolated distal radius fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(101 citation statements)
references
References 27 publications
0
101
0
Order By: Relevance
“…The average operative time was longer for the WALANT group (61.22 min) compared to the GA group (55.3 min) and the difference was statistically significant (p = 0.003). Previous studies by Dukan et al and Tahir et al found no difference in the operative time between WALANT and GA groups [ 10 , 11 ]. Both GA (n = 14) and WALANT (n = 11) groups had similar AO C2 type of radius fracture.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The average operative time was longer for the WALANT group (61.22 min) compared to the GA group (55.3 min) and the difference was statistically significant (p = 0.003). Previous studies by Dukan et al and Tahir et al found no difference in the operative time between WALANT and GA groups [ 10 , 11 ]. Both GA (n = 14) and WALANT (n = 11) groups had similar AO C2 type of radius fracture.…”
Section: Discussionmentioning
confidence: 88%
“…None of the patients in the WALANT group required conversion to general GA in contrast to Tahir et al’s study where two patients were converted to GA [ 11 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations